The Characteristics of Traffic Accident Admission Patients in Oriental Medicine Hospital - Se-Jong Kim; Jun-Hyuk Kang; Jang-Woo Park; Seo-Young Hong; Dong-Suk Heo; Il-Ji Yoon; Min-Seok Oh (Korean Pharmacopuncture Institute, 2007)
Objectives : This study was conducted to classify the TA(traffic accident) patients who admissed in Oriental Medical Hospital. Methods : We divided TA patients who admissed in Oriental Medical Hospital by age, sex, visited period after onset, impact region, disease, and chief complaint according to a patient classification table, and analyzed their characteristics. Results and Conclusion : The patients who visited within 1 week after TA numbered most(65.4%) in classification by period. Most impact region was neck(80%). Most of TA patients were suffered and treated by cervical(80%) and lumbar(56.9%) sprain.